Two-dimensional environmental profiles of growth and fumonisin production by Fusarium proliferatum on a wheat-based substrate - Cendoya, Eugenia (2014)
The effect of water activity (aW; 0.995, 0.99, 0.98, 0.96, 0.94, 0.92, and 0.90), temperature (15, 25, and 30 °C), incubation time (7, 14, 21 and 28 days), and their interactions on mycelial growth and fumonisin production on wheat-based medium by three Fusarium proliferatum strains isolated from wheat in Argentina was evaluated. Maximum growth rates were obtained at the highest aW (0.995) and 30 °C, with growth decreasing as the aW of the medium was reduced. Maximum amounts of total fumonisins (FB1, FB2 and FB3) were produced at 0.99 aW and 25 °C after 21 and 28 days of incubation for 2 strains, and at 15 °C and 0.98 aW after 28 days of incubation for the third strain. The fumonisin concentrations varied considerably depending on the aW and temperature interactions assayed. The studied strains had different fumonisin production profiles. F. proliferatum ITEM 15661 and ITEM 15664 produced FB1 and FB2 whereas F. proliferatum ITEM 15654 was able to produce FB1, FB2 and FB3. Interestingly, fumonisin production profiles for each particular strain were related to incubation temperatures. Fumonisins were produced from 15 to 30 °C and at aW values of 0.92 to 0.995 after 21 to 28 days of incubation. However at 7 and 14 days of incubation small amounts of fumonisin were produced at aW lower than 0.94. Two-dimensional profiles of aW by temperature interactions were developed from these data to identify areas where conditions indicate a significant risk from fumonisin accumulation on wheat. Temperature and aW conditions that resulted in fumonisin production are those found during wheat grain development (especially milk and dough stages) in the field. This study provides useful base line data on conditions representing a high and a low risk for contamination of wheat by fumonisins which is becoming of greater concern because this cereal is destined mainly for human consumption.